Design and implementation of a low-cost orbital shaker for laboratories - Díaz-Ronceros, Ernesto; Hernández-Amasifuen, Ángel David; Marín-Rodriguez, William Joel; Andrade Girón, Daniel; Ausejo-Sánchez, José Luis; Muñoz-Vilela, Algemiro Julio; Neri-Ayala, Abrahán Cesar (Salud, Ciencia y Tecnología, 2023)
Orbital shakers are of great importance in plant culture laboratories, however, the high cost of this equipment often makes it impossible for researchers to acquire them. Therefore, the objective of the study was to design and implement a low-cost orbital shaker for plant culture laboratories. The type of research was applied and experimental. As results, the 3D printed design of the support structure was obtained, as well as the control system based on an ATmega328P microcontroller. The range of the revolutions per minute of the orbital shaker was between 0 and 350rpm. It is concluded that the orbital shaker meets the objective set out in this research, obtaining an implementation cost of USD 153.50 US dollars